The neurobiology of brain and behavioral development - Gibb, Robbin, 1955-; Kolb, Bryan, 1947- (Academic Press, an imprint of Elsevier, 2018)
The Neurobiology of Brain and Behavioral Development provides an overview of the process of brain development, including recent discoveries on how the brain develops. This book collates and integrates these findings, weaving the latest information with core information on the neurobiology of brain development. It focuses on cortical development, but also features discussions on how the other parts of the brain wire into the developing cerebral cortex. A systems approach is used to describe the anatomical underpinnings of behavioral development, connecting anatomical and molecular features of brain development with behavioral development. The disruptors of typical brain development are discussed in appropriate sections, as is the science of epigenetics that presents a novel and instructive approach on how experiences, both individual and intergenerational, can alter features of brain development. What distinguishes this book from others in the field is its focus on both molecular mechanisms and behavioral outcomes. This body of knowledge contributes to our understanding of the fundamentals of brain plasticity and metaplasticity, both of which are also showcased in this book.